Entre espaços discursivo-biográficos: sobre as práticas de escrita de adultos surdos - ADALGISA APARECIDA DE OLIVEIRA (2021)
AMONG DISCURSIVE-BIOGRAPHIC SPACES: THE DEAF ADULTS' WRITING This work aims to destabilize the evidence effects around the hybrid nature of the writing practices of deaf adults when they mobilize the Portuguese language and make themselves authors in quotidian discursive spaces. Immersing in this thematic path (GUILHAUMOU; MALDIDIER, 2014), I adopted the Discourse Analysis of French line in dialogue with the Deaf Studies, focusing on the notions of culture and deaf identity to think on deaf as a linguistic difference, on LIBRAS as L1, and on Portuguese as a second language. In a transdisciplinary relation, I resort to biographical criticism as a way of building a “creative freedom” (SOUZA, 2011) in a comparison between a self writing, as a teacher and a researcher, in face of the writing conditions of 8 deaf students who attend high school in a State Center for Youth and Adult Education (EJA), located in Campo Grande-MS, and a reading gesture (ORLANDI, 2012) of comments produced by internet users on Danrley Oliveira and Larissa Jorge YouTube's channels about deaf's writing. With the produced discursive archive, the study outlines as corpus the regularities and dispersions (FOUCAULT, 2010) that historicize the relation between the public policies in force for inclusive education for deaf people and its implementation in the investigated context. In the process, by portraying my memories, and enunciating an unknown path, I reframe my own life and that of the other. Starting with myself, as a professional of the Specialized Educational Service, I go through memories that enrich my trajectory, by appropriating the experiences that mark my journey and that I relate both to my study object and to the stabilized assertions in the digital media regarding with deaf writing and its linguistic articulations in order to support and show the willingness to collaborate with the other, the deaf, as a subject of border subjectivities. As a result, I gathered information, records, examples, and experiences from an "other" way of thinking about the process of learning Portuguese by deaf students at EJA or even the way their written practices are constituted in the school space. In accordance with current concerns, claiming the urgency of promoting appropriate professional training for teachers and sign language interpreters, besides the implementation of language policies that demystify the distortion of the written practices of deaf students is to assume the commitment to deconstruct stigmas and provide better acquisition of LIBRAS for listeners. Keywords: Text production. Deaf people. Portuguese as a second language. High School. Discursive regularities.